Characterization of CRISPR-Cas Systems in Clinical Klebsiella pneumoniae Isolates Uncovers Its Potential Association With Antibiotic Susceptibility - Li, Hsin-Yu; Kao, Cheng-Yen; Lin, Wei-Hung; Zheng, Po-Xing; Yan, Jing-Jou; Wang, Ming-Cheng; Teng, Ching-Hao; Tseng, Chin-Chung; Wu, Jiunn-Jong (Frontiers in Microbiology, 2018)
Prokaryotic CRISPR-Cas systems limit the acquisition of genetic elements and provide immunity against invasive bacteriophage. The characteristics of CRISPR-Cas systems in clinical Klebsiella pneumoniae isolates are still unknown. Here, 97 K. pneumoniae genomes retrieved from the Integrated Microbial Genomes & Microbiomes genome database and 176 clinical isolates obtained from patients with bloodstream (BSI, n = 87) or urinary tract infections (UTI, n = 89) in Taiwan, were used for analysis. Forty out of 97 genomes (41.2%) had CRISPR-Cas systems identified by the combination of CRISPRFinder and cas1 gene sequence alignment. The phylogenetic trees revealed that CRISPR-Cas systems in K. pneumoniae were divided into 2 types (type I-E, 23; subtype I-E*, 17) based on the sequences of Cas1 and Cas3 proteins and their location in the chromosome. The distribution of type I-E and I-E* CRISPR-Cas systems was associated with the multilocus sequence typing (MLST) and the pulsed-field gel electrophoresis results. Importantly, no CRISPR-Cas system was identified in published genomes of clonal complex 258 isolates (ST11 and ST258), which comprise the largest multi-drug resistant K. pneumoniae clonal group worldwide. PCR with cas-specific primers showed that 30.7% (54/176) of the clinical isolates had a CRISPR-Cas system. Among clinical isolates, more type I-E CRISPR-Cas systems were found in UTI isolates (BSI, 5.7%; UTI, 11.2%), and subtype I-E* CRISPR-Cas systems were dominant in BSI isolates (BSI, 28.7%; UTI, 15.7%) (p = 0.042). Isolates which had subtype I-E* CRISPR-Cas system were more susceptible to ampicillin-sulbactam (p = 0.009), cefazolin (p = 0.016), cefuroxime (p = 0.039), and gentamicin (p = 0.012), compared to the CRISPR-negative isolates. The strains containing subtype I-E* CRISPR-Cas systems had decreased numbers of plasmids, prophage regions, and acquired antibiotic resistance genes in their published genomes. Here, we first revealed subtype I-E* CRISPR-Cas system in K. pneumoniae potentially interfering with the acquisition of phages and plasmids harboring antibiotic resistance determinants, and thus maintained these isolates susceptible to antibiotics.